341 Risk of lung cancer in miners and quarry workers in a pooled analysis of case-control studies. (11th October 2013) - Pesch, B P; Kendzia,; Taeger,; Behrens,; Hadad, El; Olsson,; Dahmann,; Straif,; Schüz,; Brüning,
Abstract : Objectives: Epidemiological studies have indicated an increased lung cancer risk among miners. We present estimates of the lung cancer risk in miners and quarry workers using a pooled database of case-control studies (http://synergy.iarc.fr ). Methods: This analysis included occupational and smoking histories of 15, 483 male lung cancer cases and 18, 388 controls from 16 case-control studies of the SYNERGY project. Miners and quarry workers were identified from the International Standard Classification of Occupations (ISCO 1968). We differed between coal and ore mining using the International Standard Classification of Industries (ISIC Rev. 2). Odds ratios (OR) and 95% confidence intervals (CI) for developing lung cancer were estimated by logistic regression, adjusted for age, study centre, smoking and working in occupations known to entail a lung cancer risk. Results: A total of 696 lung cancer cases and 440 controls had worked for at least one year as miner. Ever working as miner was associated with an OR of 1.58 (95% CI 1.33 to 1.74). The majority of miners (472 cases, 311 controls) had worked in coal mining. Ever working in coal mining was associated with an OR of 1.43 (95% CI 1.20–1.70). The corresponding OR in ore mining was 1.65 (95% CI 1.03 to 2.63). Working for at least one year in quarries (79 cases and 45 controls) was associated with an OR of 1.61 (95% CI 1.05 to 2.46). We could not observe trends with duration or time since last employment as miner or quarry worker. Conclusions: Working in mines or quarries was associated with an elevated lung cancer risk. We found no trend by duration of employment. These results were derived from job titles and industry codes with detailed information on smoking and other occupations hold during lifetime. Exposure to quartz or coal dust and the prevalence of silicosis could not be evaluated.